Development of pop-up book media based on project-based learning in mathematics learning about flat shapes in elementary schools - Ika Feny Nur Aini; Ni Luh Sakinah Nuraini; Yuniawatika Yuniawatika (University of Muhammadiyah Malang, 2023)
Flat building materials have very diverse materials and are considered the most difficult for students to understand. One of the failure factors that occur in students learning is the role of teachers and learning media that is less than optimal. The conditions that occur at SDN Mergosono 1 Malang City which experiences limited learning media to support mathematics learning so students have difficulty in understanding flat building material. Therefore, efforts are needed to optimize the use of media and learning models. This research aims to develop project-based learning-based pop-up book media on grade II elementary school flat building material with valid, practical, and interesting. This development research method uses the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The validation results of material experts obtained a percentage of 96.28%, media experts 98.86%, and teachers on average 98.33% by getting a very valid category. Student responses in small-scale and large-scale trials obtained an average percentage of 96.28% with very interesting and very practical criteria. So, it can be concluded that project-based learning-based pop-up book media in 2nd grade of elementary school flat building material is very feasible to use.